The Mutagenic Activity of High-Energy Explosives; Contaminants of Concern at Military Training Sites - McAllister, Jennifer E. (Université d'Ottawa / University of Ottawa, 2011)
The genotoxicity of energetic compounds (i.e., explosives) that are known to be present in contaminated soils at military training sites has not been extensively investigated. Thus, the Salmonella mutagenicity and Muta(TM)Mouse assays were employed as in vitro assays to examine the mutagenic activity of twelve explosive compounds, as well as three soil samples from Canadian Forces Base Petawawa. Salmonella analyses employed strains TA98 (frameshift mutations) and TA100 (base-pair substitution mutations), as well as the metabolically-enhanced YG1041 (TA98 background) and YG1042 (TA100 background), with and without exogenous metabolic activation (S9). For Salmonella analyses, the results indicate that ten of the explosive compounds were mutagenic, and consistently elicited direct-acting, base-pair substitution activity. All three soil samples were also observed to be mutagenic, eliciting direct-acting, frameshift activity. Mutagenic potencies were significantly higher on the metabolically-enhanced strains for all compounds and soil samples. For Muta(TM)Mouse analyses on FE1 cells, the results indicate that the majority of explosive compounds did not exhibit mutagenic activity. All three soil samples elicited significant positive responses (PET 1 and PET 3 without S9, and PET 2 with S9), and although there is some evidence of a concentration-related trend, the responses were weak. Correspondence of the mutagenic activity observed with the two assay systems, for both the explosive compounds and soil samples, was negligible. The differential response is likely due to differences in metabolic capacity between the two assay systems. Furthermore, it is likely that there are unidentified compounds present in these soil samples that are, at least in part, responsible for the observed mutagenic activity. Additional testing of other explosive compounds, as well as soil samples from other military training sites, using a variety of in vitro and in vivo assays, is warranted in order to reliably estimate mutagenic hazard and subsequently assess risk to human health.
Keywords: Explosives; Soil contamination; Salmonella typhimurium; Salmonella mutagenicity assay; Flat Epithelial cell line; Muta(TM)Mouse assay